Ethnomethodology Study on The Implementation of Social Responsibility Activities at PT Pertamina Lubricants - Dwi Indriyana, Novika; Gusliana Mais, Rimi (Green Publisher Indonesia, 2024)
Financial Services Authority Regulation No. 51/POJK.03/2017, social and environmental responsibility or abbreviated as TJSL is a commitment to participate in sustainable economic development in order to improve the quality of life and the environment that is beneficial, both for the company itself, the local community, and the community in general TJSL or what we commonly know as Corporate Social Responsibility (CSR) is part of sustainable development that must be carried out by all development actors, namely the government, the community, and also the business community. This study uses a qualitative method with ethnomethodology studies to reveal the practice of CSR implementation at PT Pertamina Lubricants from 2019 to 2023. The purpose of this study is to reveal CSR practices in an effort to maintain sustainability activities at PT Pertamina Lubricants. The triple bottom line and good corporate governance approach are used in this study. Data collection was carried out through interviews, field observations, and literature studies. The results show that PT Pertamina Lubricants has transformed its CSR practices by emphasizing Creating Shared Value (CSV). CSR practices during the Covid-19 pandemic are still ongoing by implementing applicable protocols. The triple bottom line bottom line approach, namely profit, people, and planet, and good corporate governance , has also been implemented.